INSTITUTIONAL REVITALIZATION OF FISHERIES COOPERATIVES AS A MEANS OF EMPOWERING COASTAL COMMUNITIES - Nur Sulistyo Budi Ambarini; Wafiya (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
The purpose of this study was to examine and explain the revitalization of fisheries cooperative institutions that could serve as a means of empowering coastal communities. Fisheries cooperatives were institutions that functioned as a platform for their members to carry out joint economic activities in the fisheries sector. Although Indonesia’s fisheries resources were abundant and highly potential, the socio-economic life of coastal communities was generally categorized as poor and marginalized. This research was a non-doctrinal legal study using a socio-legal research approach. This paper attempted to analyze and describe the issues of revitalizing fisheries cooperative institutions that could become a means of empowering coastal communities. The results of the study showed that revitalization of fisheries cooperatives could serve as an instrument to empower coastal communities. Cooperatives, as economic institutions, also simultaneously functioned as social institutions that played a role in improving welfare. They contributed not only in economic aspects but also in social aspects through education that could enhance members’ knowledge and skills. As business entities, cooperatives gathered members based on the principle of voluntarism. Therefore, as legal entities, fisheries cooperatives needed institutional revitalization to function effectively in improving welfare and protecting the interests of their members.